Ketiadaan Batas Waktu Suspensi dan Implikasinya Terhadap Perlindungan Investor Pasar Modal Indonesia - Inda - Rahadiyan; Diah Ayu Ambarsari (Jurnal Hukum IUS QUIA IUSTUM, 2018)
The problems in this study include First, how is the regulation of suspension and its implications on the legal certainty for listed companies? Sekond, what are the implications of the absence of time limit for suspension on investor protection? Third, how is the time limit for suspension in the United States? This study used normative legal method. The results of the study indicated that First, the absence of regulation regarding the time limit for suspension by the Indonesia Stock Exchange results in the absence of legal certainty for listed companies subject to suspension. Sekond, the absence of time limit for suspension has an impact in the form of a low legal protection for investors. Third, Suspension in the United States imposed by the Securities Exchange Commission (SEC) is limited to a certain period of time. The regulated time limit for imposing suspensions in the United States provides more legal certainty for listed companies and more legal protection for investors.